Indonesian-Aceh Application Translation Design Based on Android - Shaumi, Rahmat (Lembaga KITA, 2021)
Language is a sign to communicate. In the world, there are many languages that characterize the country, for example, the State of Indonesia which has various regional languages, one of which is the Aceh language which is dominantly used by residents in the Aceh Province to communicate. The purpose of this research is to design and build an android-based digital dictionary application that can be used to make it easier to find translated vocabulary in Indonesian or in Acehnese so that they can be used in general so as to provide convenience for the user. The method used in this thesis is the prototyping method. Based on the test results on the Android-based Indonesian-Aceh application, it can be seen and can conclude several things, namely; The search system is designed to be able to display words in the text file in program code faster because it does not require large data, in the coding process using the auto-search model and an array that matches the application user input string, this dictionary application is designed using Xamarin Microsoft Visual Studio 2017 which can be exported on IOS and Windows Phone systems in a single project built.